The Development of Dusting Method for Dragon Fruit Peel as Fingerprint Visualization - Sri Adelila Sari; Ade Novita Sari Lubis (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2021)
Various fingerprint powder preparations used for fingerprints have a color or contrast and a sticky material for good adhesion. However, some chemical substrates used for fingerprint powders are toxic and have the potential to harm health. This research is essential to overcome this problem using a new natural powder , namely dragon fruit peel powder, as a latent fingerprint development that was simple, non-toxic, and cheaper than commercial used fingerprint powder. Fingerprint development was carried out on non-porous surfaces (aluminium foil, CD, glass preparations) and porous surfaces (HVS paper, spectra paper, paperboard). This study used 90 fingerprint samples based on ethnicity (Batak, Javanese, Malay), blood type, and gender. The development of fingerprints using dragon fruit peel powder resulted in clear visualization on the surface of aluminium foil and glass preparations with sizes of 100 and 200 mesh. Meanwhile, fingerprints on the paper surface resulted in poor visualization because the protrusions of the fingerprints were not visible. The most dominant fingerprint patterns based on ethnicity, blood group, and gender were the loop pattern, then the whorl, and the smallest arch, respectively.